Exploring Lactic Acid Bacteria from Aceh’s Keumamah Fish as Potential Natural Antibiotics to Inhibit Escherichia Coli - Periskila Dina Kali Kulla; Zulwanis Zulwanis; Suryani Musa (Indonesian Journal of Global Health Research, 2025)
Aceh is known for its abundant fishery resources, particularly tuna, which has an annual production of 7,903 tons. However, tuna is highly perishable, necessitating effective preservation methods to maintain its quality. Keumamah fish, a traditional Acehnese dish, is renowned for its dried texture, allowing it to be stored for extended periods and making it a common choice for various events. Objective: This study aims to identify lactic acid bacteria (LAB) present in keumamah fish that contribute to the fermentation process and serve as potential sources of natural antibiotics to inhibit the pathogenic bacteria Escherichia coli. Method: Lactic Acid Bacteria (LAB) isolation was conducted using dilution and inoculation techniques on MRS agar media supplemented with CaCO3. The results indicated that the inhibition zones of the isolated LAB were as follows: isolate IK4 showed an inhibition zone of 9.81 mm, isolate IK5 exhibited 11.3 mm, isolate IK6 had 9.4 mm, and isolate IK9 displayed 10.56 mm. Based on Gram staining and biochemical tests (temperature, pH, and salt tolerance), seven isolates were classified into three genera: Lactobacillus (IK3, IK5, and IK7), Enterococcus (IK4, IK6, and IK9), and Leuconostoc (IK8).